Penerapan Undang-Undang Nomor 35 Tahun 2009 Tentang Narkotika Terhadap Anak Pengedar Narkotika di Kota Medan - Dwi Mika Elencia Sirait; Ojak Nainggolan (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2024)
Implementation of Law no. 35 of 2009 concerning Narcotics in Medan City is an important issue in the context of legal protection for children involved as narcotics dealers. This research aims to analyze how the narcotics law is applied in cases involving children, as well as things that are considered in the law enforcement process and how criminal proceedings are carried out in the juvenile criminal justice system. This research provides an in-depth understanding of the application of special regulations, namely Law no. 35 of 2009 concerning Narcotics, while still considering Law no. 11 of 2012 which regulates the Juvenile Criminal Justice System. This approach aims to ensure legal protection for children involved in narcotics crimes, so that the law can be applied fairly and protect children's rights. This research utilizes empirical juridical legal methods, where the main data is obtained through direct interviews with judges serving at the Special Class IA Medan District Court, thus enabling researchers to obtain relevant and in-depth perspectives regarding the application of this law in real practice in the judicial environment.